Development of Formative Tests Based on Self-Directed Learning-Oriented Assessment for Mathematics in Junior High School - Ihsanul Amin; Chairil Faif Pasani; Kamaliyah Kamaliyah; Zainudin Hassan (Universitas Lambung Mangkurat, 2026)
Formative assessment practices in schools often focus on Assessment for Learning (AfL) but insufficiently facilitate Assessment as Learning (AaL), limiting students’ reflection and self-assessment. To address this, Self-directed Learning Oriented Assessment (SLOA) is employed as an approach integrating self-assessment to foster self-directed learning capacities by aligning the functions of assessment of, for, and as learning. This study aimed to develop valid, practical, and effective SLOA-based formative tests for junior high school mathematics. The study employed a research and development (R&D) approach using the ADDIE model. The research was conducted in a single seventh-grade class at a junior high school in Barito Kuala under the Kurikulum Merdeka, involving 25 students and one mathematics teacher. Data were collected through expert validation sheets, a teacher practicality questionnaire, and students’ mastery of learning outcomes. The results indicated that the developed formative tests and self-assessment sheets were very valid, with mean scores of 3.47 and 3.36, respectively. The product was categorized as very practical, obtaining a practicality percentage of 98%. In terms of effectiveness, the product was categorized as effective, with an average classical mastery reached of 61.3%, derived from three test packages showing a consistent upward trend in student performance. The progressive increase in students’ mastery and metacognitive accuracy suggests that integrating structured self-assessment into formative testing supports learning achievement and reflective awareness. This study implies that SLOA-based formative tests can serve as a strategic framework to foster student independence, provided that they are implemented with adequate instructional time and systematic feedback cycles.